Small area variation in the utilization of common medical tests and consultations in Ontario, Canada. (2017) - Quail, Jacqueline; Anderson, Maureen; Osman, Meric; Oliveira, Claire de; Wodchis, Walter; Muhajarine, Nazeem; Pruden, Kathie Nansel; McLeod, Valerie; Baetz, Marilyn; Teare, Gary; Lafontaine, Tania; Pelly, Judy; et al.
No abstract available